(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Solar-powered air conditioning systems are often extremely cost-effective when used in residential and commercial buildings. Today, energy is the greatest issue confronting humanity. Energy consumption is increasing due to the growing global population and the developing nations’ economies. Solar energy is therefore the main alternative energy source that can meet the energy demand. For warm and humid regions, sustained comfort within the air conditioner is extremely important. Due to the intensive usage of the air conditioning system, the energy demand in mid summer increases. In order to overcome this shortfall in CO2 emissions which contributes to global warming, the country faced an enormous problem in the electricity scarcity, while the vapor compression air conditioning system disturbs the stratospheric layer of ozone because of the use of chlorofluorocarbons (CFCs) in coolants. Solar energy air cooling may be utilized with absorption chillier with solution of lithium bromide and water. The solar-powered air conditioning system helps to reduce the usage of fossil fuel. Liquid Dry Air Conditioning (LDAC) is one of the most efficient and environmentally friendly air conditioning technologies. LDAC may be powered by minimal energy, such as solar electricity. The usage of Si solar cells with structured glass packing covers improved conversion efficiency by 6% at normal angle of incidence.